2017
DOI: 10.1101/166579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Locomotor and Reinforcing Effects of Pentedrone, Pentylone and Methylone in Rats

Abstract: The broad diversity of synthetic cathinone psychostimulant drugs that are available to users complicates research efforts to provide understanding of health risks. Second generation cathinones pentedrone and pentylone are distinguished from each other by the 3,4-methylenedioxy structural motif (which distinguishes methamphetamine from 3,4-methylenedioxymethamphetamine) and each incorporates the α-alkyl chain motif contained in the transporter-inhibitor cathinones (3,4-methylenedioxypyrovalerone (MDPV), α-pyrro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 42 publications
5
11
0
Order By: Relevance
“…The effects of α-PVP on temperature were small and failed to reach significance, although racemic α-PVP tended to increase body temperature. Our results agree with the findings of Nelson et al, 26 Finally, confirming what others have shown for racemic α-PVP, 20,24,[28][29][30][31][32][33] rats self-administered α-PVP at doses similar to racemic MDPV. 45 Self-administration was acquired rapidly with α-PVP, and the drug produced a typical inverted U-shaped dose-effect function comparable with other psychomotor stimulants.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The effects of α-PVP on temperature were small and failed to reach significance, although racemic α-PVP tended to increase body temperature. Our results agree with the findings of Nelson et al, 26 Finally, confirming what others have shown for racemic α-PVP, 20,24,[28][29][30][31][32][33] rats self-administered α-PVP at doses similar to racemic MDPV. 45 Self-administration was acquired rapidly with α-PVP, and the drug produced a typical inverted U-shaped dose-effect function comparable with other psychomotor stimulants.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, confirming what others have shown for racemic α‐PVP, 20,24–24,28–33 rats self‐administered α‐PVP at doses similar to racemic MDPV 45 . Self‐administration was acquired rapidly with α‐PVP, and the drug produced a typical inverted U‐shaped dose‐effect function comparable with other psychomotor stimulants.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These compounds largely act as inhibitors of monoamine transporters and, in general, are selective for the dopamine transporter (DAT) over the norepinephrine (NET) or serotonin (SERT) transporters (e.g., Eshleman et al 2017;Gannon et al, 2018a;Meltzer et al, 2006). Several of the compounds are self-administered, including αpyrrolidinopropiophenone (α-PPP; Aarde et al, 2015;Gannon et al, 2018b), 4′-methyl-α-pyrrolidinopropiophenone (4′-MePPP; Huskinson et al, 2017), α-pyrrolidinovalerophenone (α-PVP; Huskinson et al, 2017;Javadi-Paydar et al, 2018), 3,4-methylenedioxy-pyrovalerone (MDPV; Aarde et al, 2013;Gannon et al, 2017Gannon et al, , 2019Watterson et al, 2014), α-pyrrolidinopentiothiophenone (α-PVT; Cheong et al, 2017), and α-pyrrolidinohexiophenone (α-PHP; Javadi-Paydar et al, 2018). MDPV (Atehortua-Martinez et al, 2019;Karlsson et al, 2014;King et al, 2015) and α-PVT (Cheong et al, 2017) produced a conditioned place preference, and MDPV increased intracranial self-stimulation (ICSS; Bonano et al, 2014;Geste et al, 2018;Watterson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, brain regions exhibiting high HIV-1 mRNA expression also correspond with neuroanatomical alterations previously observed in the HIV-1 Tg rat. Broadly, the HIV-1 Tg rat exhibits synaptic dysfunction 32,35,44 , neurotransmitter system alterations 68,36 , and neuroinflammation 39 ; deficits which have been implicated in the pathogenesis of HAND. More specifically, profound synaptic dysfunction has been observed in both pyramidal neurons from layers II-III of the mPFC 32 and medium spiny neurons from the NAc 35,44 evidenced by alterations in dendritic branching complexity and synaptic connectivity in HIV-1 Tg animals relative to controls.…”
Section: Discussionmentioning
confidence: 99%